PROSES REBRANDING STARTUP PINTAR.CO - Siadari, Roulina; Surayya Ulfa, Nurist; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Branding involves a series of marketing communication activities aimed at enhancing a brand by integrating its core concept into all advertising and stakeholder interactions. Harukaedu, a startup edutech company, faced challenges with its marketing communications due to its three independent business units. To address this, the company undertook a rebranding process to unify its identity and streamline communication strategies. Using a qualitative case study approach and constructivist paradigm, the research examined the brand change process based on General Model Planned Change, Brand Management, and Corporate Rebranding theories. The findings reveal that the company executed a revolutionary rebranding through a structured, step-by-step approach to rebuild its brand and image. The rebranding process included entering & contracting, diagnosing, planning, and implementing, which involved repositioning, renaming, redesigning, launching, and evaluating, before concluding with institutionalizing change.